Levothyroxine Therapy Adequacy, Dose Estimation and Vitamin D Effect Assessment in a Sample of Iraqi Female Patients with Different Causes of Hypothyroidism - Ban A. Al-Shimmran (Iraqi Journal of Pharmaceutical Sciences, 2020)
Exogenous levothyroxine dose modulation and euthyroidism achievement is a persistent challenge in clinical settings. This study strives to assess the adequacy of treatment and identify the patients’ factors that can be used to estimate the euthyroid levothyroxine dose. A secondary objective was to assess vitamin D supplementation impact on thyroid status.